Flow-Synchronized Nasal Intermittent Positive Pressure Ventilation for Infants <32 Weeks' Gestation with Respiratory Distress Syndrome. (27th November 2012) - Gizzi, C.; Papoff, P.; Giordano, I.; Massenzi, L.; Barbàra, C. S.; Campelli, M.; Panetta, V.; Agostino, R.; Moretti, C.
Abstract : Aim . To evaluate whether synchronized-NIPPV (SNIPPV) used after the INSURE procedure can reduce mechanical ventilation (MV) need in preterm infants with RDS more effectively than NCPAP and to compare the clinical course and the incidence of short-term outcomes of infants managed with SNIPPV or NCPAP. Methods . Chart data of inborn infants <32 weeks undergoing INSURE approach in the period January 2009–December 2010 were reviewed. After INSURE, newborns born January –December 2009 received NCPAP, whereas those born January–December 2010 received SNIPPV. INSURE failure was defined as FiO2 need >0.4, respiratory acidosis, or intractable apnoea that occurred within 72 hours of surfactant administration. Results . Eleven out of 31 (35.5%) infants in the NCPAP group and 2 out of 33 (6.1%) infants in the SNIPPV group failed the INSURE approach and underwent MV (P < 0.004 ). Fewer infants in the INSURE/SNIPPV group needed a second dose of surfactant, a high caffeine maintenance dose, and pharmacological treatment for PDA. Differences in O2 dependency at 28 days and 36 weeks of postmenstrual age were at the limit of significance in favor of SNIPPV treated infants. Conclusions . SNIPPV use after INSURE technique in our NICU reduced MV need and favorably affected short-term morbidities of our premature infants.